Modelling and anaysis of energy absorption capacity of 3D printed stucture design - Khor, Heng Kee (Nanyang Technological University, 2022)
3D printing has becoming more and more popular due to its manufacturing benefits. The strength and performance of the 3D printed object depends highly on the structural design used for printing. Therefore, it is crucial to have a structural design that provide promising energy absorption and overall performance so as to set as an alternative way of manufacturing compared to conventional. This project focuses on creating new 3D design structural to increase its overall performance especially on achieving higher energy absorption capabilities. In this project, various reviews will be done to pick up favourable structural design traits that could be useful in forming the new structural design. A new design structure created make use of honeycomb and struts to increase overall performance. On top of that, finite element analysis would be utilised to help understand the performance of the newly designed model. Popular simulation software such as ANSYS will be used to simulate the behaviour of the model when under various tests. In this project, compression test and impact drop test will be the 2 key test to understand the behaviour and performance of the model. From the simulation results, the overall energy absorption is at a decent rate and with high dissipating energy. The new designed structure provides good impact absorption behaviour such that the movement of the model upon impact avoid excessive deformation. From the compression results, it shows the overall behaviour of the model when under high loading. On the average, the model is able to withstand compression 20% compression with respect to its height without excessive breakage of model at all direction. The highest compression is able to hit half of its height of 50% at the side direction due to configuration of model such that honeycomb can withstand excessive compression with different orientation.